Determination of the MEC90 of Oxycodone for Preventing Perioperative Shivering in Pregnant Patients Undergoing Caesarean Delivery with Neuraxial Anaesthesia: A Biased-Coin up-and-Down Sequential Allocation Trial - Lu X; Chen K; Xuan Y; Shen M; Lei W; Huang Y; Sun J (Drug Design, Development and Therapy)
Xinlei Lu,1,* Kaiyu Chen,1,2,* Ye Xuan,1,2 Mengting Shen,1,2 Weiping Lei,1 Yaqin Huang,1 Jianliang Sun1 1Department of Anaesthesiology, Affiliated Hangzhou First People’s Hospital, School of Medicine, Westlake University, Hangzhou, People’s Republic of China; 2The Fourth School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianliang Sun, Department of Anaesthesiology, Affiliated Hangzhou First People’s Hospital, School of Medicine, Westlake University, Hangzhou, People’s Republic of China, Email jxmzsjl@163.comBackground: Perioperative shivering is a common adverse reaction to neuraxial anaesthesia. Intravenous oxycodone can be used to prevent shivering. However, few trials have been conducted on the use of oxycodone to prevent shivering, and the optimal dose is unknown. This study aimed to determine the optimal dose (90% minimum effective concentration [MEC90]) of intraoperative oxycodone to prevent shivering during caesarean section.Methods: This study was designed by the biased-coin up-and-down method. We recruited pregnant women who underwent caesarean section under combined spinal–epidural anaesthesia. Oxycodone was administered intravenously after the delivery of the foetus. The initial dose was 80 μg/kg, and subsequent dose adjustments were determined by up-and-down sequential allocation using a biased-coin design based on the response of the previous patient. The primary outcome was the MEC90 for oxycodone injection based on the success or failure of the shivering-preventing dose.Results: Fifty patients were enrolled in the study. The oxycodone dose ranged from 80 to 95 μg/kg. The estimated MEC90 (95% confidence interval [CI]) for preventing shivering was 88.1 μg/kg (81.5– 92.5 μg/kg). The patient’s postoperative temperature was 36.5 ± 0.2 °C. The incidence of intraoperative traction pain was 12%. The 5-min and 30-min Ramsay sedation scores were 3 (3– 4) and 3 (3– 3), respectively. The 2-h and 6-h postoperative VAS scores were 3 (2– 3) and 4 (3– 5), respectively. The patient’s anaesthesia satisfaction score was 5 (4– 5). The incidence of respiratory depression was 2%, and the incidence of nausea and vomiting was 16%.Conclusion: The MEC90 of intraoperative intravenous oxycodone for the prevention of shivering in women undergoing caesarean section with neuraxial anaesthesia was 88.1 μg/kg (95% CI: 81.5– 92.5 μg/kg).Keywords: MEC90, oxycodone, perioperative shivering, caesarean delivery, neuraxial anaesthesia